A integração de crenças e experiências religiosas e espirituais na terapia cognitivo-comportamental: apresentação e análise crítica do trabalho realizado pelo Prof. Dr. Harold G. Koenig e equipe do Centro de espiritualidade, teologia e saúde da Universidade Duke - Hamazaki, Edson Sigueyoshi (2021)
Prof. Dr. Harold G. Koenig and team, within the scope of the Center for Spirituality, Religiosity and Health at Duke University, developed a broad research project, with the purpose of developing a treatment protocol for a Religiously Integrated Cognitive Behavioral Therapy, creating what they called Religious Cognitive Behavioral Therapy (RCBT). The aim of this work was to, critically examine and present this research to the Brazilian public interested in the impact of religiosity and spirituality on mental health treatment. The research developed by Koenig and collaborators, was a randomized, multicenter clinical trial, involving treatment protocols for depression among religious believers with chronic diseases, members of the five major world religions: Christianity, Judaism, Buddhism, Hinduism and Islamism.The study compared RCBT, with secular psychotherapy in order to verify if the treatment could reverse physiological changes induced by depression. The majority of 10 50- minute sessions over 12 weeks were conducted by telephone (94%). 132 patients were randomized to either CBT (n = 67) and CBTR (n = 65). The results indicated that CBTR was as effective as CBT in remission of depression, indicating a small superiority when patients have intrinsic religiosity. There was no pattern of association between religious experiences and practices (RPE) and inflammatory cytokines, or stress hormone markers, in the clinical analyzes performed. However, the psychotherapy protocol developed by CETS aldo presents challenges. Although feasible for a randomized clinical study, the highly structured protocol makes it difficult to pernonalize the treatment for each patient and disregards complex phenomena such as multiple religious belonging and religious switching, hybridism, crises of faith and processes of desconversion, as well as the growing phenomenon of spirituality without religion. There is stil little consideration for others factors, such as cultural and denominational differences within the same religious affiliation. We conclude by recognizing the importance of the religious/spiritual dimension in psychotherapy and by pointing out the relevance of considering the aforementioned aspects in the development of future research and psychotherapy protocols